(untitled) (Journal of Kathmandu Medical College, 2017)
Background: The premature rupture of membrane is a major risk factor for the early onset sepsis in neonates. It increases the risk of serious neonatal infection to one percent, compared to 0.5% for women with intact membrane. There is a conventional practice of using antibiotics in most of the babies with maternal history of premature rupture of membrane >18 hours. It is noticed that all the babies may not need prophylactic antibiotics in these conditions and there should be judicial use of antibiotics in babies with maternal history of premature rupture of membrane. Objectives: To identify the risk factors for use of antibiotics in newborn babies born at Kathmandu Medical College Teaching Hospital with maternal history of premature rupture of membrane and to observe the outcome of the babies. Method: This is a prospective observational study done at Kathmandu Medical College Teaching Hospital. All newborns with maternal history of premature rupture of membrane for more than 18 hours were screened for neonatal sepsis and managed according to the treatment protocol. Ethical clearance was obtained and data were analyzed in statistical package for social science 16. Results: Among 160 cases included, 99 (62%) mothers received antibiotics for premature rupture of membrane and only 54 (35%) babies’ required antibiotics. Among them 30 babies required oral antibiotics, 20 babies required injectable antibiotics and four babies required both antibiotics(oral and injectable), which is statistically signifi cant (p value 0.03 ). Conclusion: This study has highlighted that every babies may not need antibiotics with maternal history of premature rupture of membrane. The use of antibiotics to mother for PROM before delivery has a signifi cant benefi ciary effect to babies reducing incidence of sepsis. Journal of Kathmandu Medical College, Vol. 5, No. 1, Issue 15, Jan.-Mar., 2016, Page: 3-10